Changing hearts instead of changing minds – another take on climate action - BinBin J. Pearce (Global Social Challenges Journal)
This piece elaborates on a ‘new way of thinking’ (Einstein, 1946) that would contribute to overcoming the challenge of climate change and its impacts. This ‘new way’ will have us go beyond using facts and figures alone to persuade and cajole. It will have us stretching our moral imagination (Johnson, 2016) and empathising with people very different from ourselves. It will have us investing in processes of exchange which support the co-creation of knowledge and the future we want together.